2018
DOI: 10.1371/journal.pone.0193635
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic drug use as indicator of mental health in adolescents affected by a plexus injury at birth: A large population-based study in Sweden

Abstract: Chronic handicap in early life may have a long-term impact on children’s psychosocial well-being. Here, we investigated whether Brachialis Plexus Birth Injury (BPBI)—an unpredictable injury at birth—is associated with worse mental health later on, as indicated by prescription and use of psychotropic drugs in adolescence. We explored further whether this association is different depending on socioeconomic characteristics of the child’s family, as well as sex. Of the 641 151 children born to native parents in Sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…These activities were questioned because they are usual to Finnish population and require bimanual function. On the other hand, Bae et al 24 reported that NBPP children were similar to the published normative pediatric data: 75 (88%) of NBPP children played sports, and 61 (72%) were involved in individual sports and 54 (63%) in team ones. These results showed a representative participation in several sports, including those requiring upper extremity dexterity, such as baseball, swimming, and gymnastics.…”
Section: Nbppg Mean±sdsupporting
confidence: 57%
See 2 more Smart Citations
“…These activities were questioned because they are usual to Finnish population and require bimanual function. On the other hand, Bae et al 24 reported that NBPP children were similar to the published normative pediatric data: 75 (88%) of NBPP children played sports, and 61 (72%) were involved in individual sports and 54 (63%) in team ones. These results showed a representative participation in several sports, including those requiring upper extremity dexterity, such as baseball, swimming, and gymnastics.…”
Section: Nbppg Mean±sdsupporting
confidence: 57%
“…This information may be useful for clinicians to notice that NBPP negatively affects the QOL of affected children in multiple aspects, based on perception of their parents, including the emotional impact on their families. Psouni et al 24 verified that children who suffered a NBPP are at a higher risk of using psychotropic medication in adolescence, compared to the Control Group. Furthermore, female adolescents and individuals with lower family income were at higher risk of being prescribed and using psychotropic drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be remembered that some individuals may take psychotropics (e.g., sedative-hypnotics) without a specific psychiatric diagnosis and some subjects may take these medications for non-psychiatric disorders. Hence, the number of subjects with a psychiatric history and the number of subjects currently taking psychotropic medications may not be equal [28,29].…”
Section: Psychiatric History and Current Treatment With Psychotropic Medicationsmentioning
confidence: 99%
“…To address this aim, female patients referred to a tertiary care urogynecological center by their family physicians for further diagnosis and treatment of OAB were screened for a history of psychiatric disorders [26,27] and the type and number of psychotropic medications currently being taken. Notably, psychotropic medications are commonly used as a simple indicator of mental health problems in different populations of patients [28,29].…”
Section: Introductionmentioning
confidence: 99%